Assembled anti-adhesion polypropylene mesh with self-fixable and degradable in situ mussel-inspired hydrogel coating for abdominal wall defect repair. (3rd October 2018) - Hu, Wanjun; Zhang, Zhigang; Lu, Shenglin; Zhang, Tianzhu; Zhou, Naizhen; Ren, Pengfei; Wang, Faming; Yang, Yang; Ji, Zhenling
Abstract : Construction of assembled anti-adhesion polypropylene mesh through in situ coating with self-fixable and degradable hydrogels. Abstract : Abdominal adhesion to polypropylene (PP) mesh remains one of the major complications in hernia repair. Thus, a challenge exists to endow PP mesh with powerful anti-adhesion properties in hernia repair. To investigate potential options, the assembled PP mesh was developed with effective anti-adhesion properties through an in situ coating of the mesh surface with self-fixable and biodegradable mussel-inspired hydrogels. Through mixing oxidized-carboxymethylcellulose functionalized with dopamine (OCMC-DA) with carboxymethylchitosan (CMCS), a layer of hydrogel (OCMC-DA/CMCS) can be formed in situ on the PP mesh without the addition of crosslinking agents; the dopamine then acts as an immobilization group to fix these hydrogels to the PP mesh and the tissue surface. In this way, the assembled PP mesh (OCMC-DA/CMCS/PP) was obtained. The properties of the OCMC-DA/CMCS hydrogels were optimized, and the OCMC-DA4/CMCS hydrogel was selected to construct the assembled PP mesh. The lap-shear test revealed that OCMC-DA4/CMCS has tissue-adhesive properties. In vitro cell tests proved the excellent biocompatibility of the hydrogel. An optimized bioabsorption time and significant anti-adhesion properties were demonstrated through an in vivo test with a rat model. The adhesion area and tenacity of the OCMC-DA4/CMCS/PP group were more than 80% lower than those of the native PP mesh group and created a slightly inflammatory reaction.